Identification of the Influence of Socio, Demographic, and Economic Factors on Domestic Water Consumption Patterns (A Case Study: Bandar Lampung City, Indonesia) - Dion Awfa; Ainan Azka; Yulisa Putri; Nasrul Putra; Ahmad Daudsyah Imami; Rifka Noor Azizah; Wisnu Prayogo (Universitas Diponegoro, 2023)
Urban water management efforts are essential in encouraging the fulfillment of the SDGs targets. One action that can be done is to approach the calculation of the actual water consumption value. This research conducted a survey of domestic water consumption in Bandar Lampung City to obtain comprehensive information. Bandar Lampung City was chosen because it is one of the cities on the island of Sumatra with a high economic growth rate. Lampung Province is the top 3 province in Sumatera Island with the higher Gross Domestic Product Growth on 2022, with Bandar Lampung as its capital city. Furthermore, water consumption patterns were analyzed for various activities, socio demographic conditions, and the community's economy. The results showed that of the 404 samples, the average water usage was 195.08 liters/person/day, with the dominant activities in use including bathing (66.84 liters/person/day), flushing the toilet (35.71 liters/person) / day), and ablution (29.74 liters/person/day). Furthermore, the variable number of family members in one house and income level have significant different on total domestic water consumption. The results obtained in this study are expected to assist in making decisions regarding urban water management plans.